Occupational exposure to volatile organic compounds affects microRNA profiling: Towards the identification of novel biomarkers. (2020) - Sisto, Renata; Capone, Pasquale; Cerini, Luigi; Paci, Enrico; Pigini, Daniela; Gherardi, Monica; Gordiani, Andrea; L'Episcopo, Nunziata; Tranfo, Giovanna; Chiarella, Pieranna
Graphical abstract: Highlights: Exposure to volatile organic compounds represents a threat for workers' health and safety, even using protective equipment. Spray-painting exposure is at higher risk than roller-painting. Exposure to organic solvents may induce DNA and RNA oxidation, urine metabolite excretion and miRNA up- or down-regulation. miR-589-5p and miR-941, miR-146b-3p and miR-27a-3p have been identified as potential biomarkers of effect in exposed workers. KEGG pathway analysis showed that miRNA-1, related to lung cancer, is significantly downregulated in exposed workers. Abstract: In the framework of a project aimed at finding novel predictive biomarkers of VOCs exposure-related diseases, the effect of exposure to ethylbenzene, toluene, and xylene has been analyzed in a group of painters (spray- and roller-painters) working in the shipyard industry. Airborne levels of solvents were higher in spray- than in roller-painters, and comparable to the Occupational Exposure Limits (OELs), particularly for toluene and xylene. The urinary concentration of each volatile organic compound (VOC) and of the corresponding metabolites were also concurrently measured. A set of oxidative stress biomarkers, i.e., the products of DNA and RNA oxidation, RNA methylation, and protein nitration, were measured, and found significantly higher at the end of the work shift. MicroRNA (MiRNA) expression was analyzed in the VOC-exposed workers and in a control group, finding 56 differentially expressed (DE) miRNAs at a statistically significant level (adjusted p ≤ 0.01). The Receiver-Operating Characteristic curves, computed for each identified miRNA, showed high sensitivity and specificity. A pathway analysis in the Kyoto Encyclopedia of Genes and Genomes (KEGG) showed that miRNA-1, which was found downregulated in exposed workers, is involved in the lung cancer oncogenesis. A subset of 10 miRNAs (out of the 56 DE) was selected, including those with the highest correlation to the urinary dose biomarkers measured at the end of work-shift. Multivariate ANOVA analysis showed a statistically significant correlation between the urinary dose biomarkers (both the VOCs urinary concentration and the VOCs' metabolite concentration), and the identified miRNA subset, indicating that the exposure to low VOC doses may be sufficient to activate the miRNA response. Four miRNAs belonging to the subset strongly related to the VOCs and VOCs' metabolites concentration were individuated, miR-589-5p, miR-941, miR-146b-3p and miR-27a-3p, with well-known implications in oxidative stress and inflammation processes.